Physiology of sport and exercise - Kenney, W. L.; Wilmore, J.; Costill , D. (Human Kinetics, 2015)
Product Description Physiology of Sport and Exercise, Sixth Edition With Web Study Guide, frames research findings in physiology in a reader-friendly format, making this textbook a favorite of instructors and students alike. This resource offers a simple way for students to develop an understanding of the body`s abilities to perform various types and intensities of exercise and sport, to adapt to stressful situations, and to improve its physiological capacities.